Assessing mental health and service needs among refugees in Malaysia - Shaw, Stacey Anne; Pillai, Veena; Ward, Kaitlin P. (John Wiley & Sons, 2018)
Refugees in Malaysia often experience economic insecurity and poverty, poor health, poor mental wellbeing and limited legal rights. Using a survey with quantitative measures and open-ended questions, we assessed socio-demographic characteristics, mental health (RHS-15), and service needs, including interest in group support services, among 86 Dari- and Arabic-speaking refugees living in Kuala Lumpur. High levels of emotional distress were found, as nearly all participants scored positive for distress and average scores were 2.5 times above the cut-off signifying distress. Distress scores did not vary based on most factors examined, although being married was associated with lower levels of distress. All but one participant expressed interest in participating in a support group. Barriers to potential participation included childcare, sickness and transportation. Additional mental health and social supports are needed among refugees residing in Malaysia. Key Practitioner Message: • Emotional distress is high among Dari- and Arabic-speaking refugees sampled in Malaysia; • Participants expressed strong interest in accessing supportive mental health services, including group supports.